Roman denarius triumviri monetales 82 B.C.: on the use of the method of comparing stamps in the coin issue of antiquity and the middle ages - S.V. Belousov (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки)
Background. In recent years, the method of stamp analysis of coins has been in-creasingly used in historical and numismatic research, which makes it possible to model many aspects of economic development and reconstruct various processes of historical real-ity with their help. The stamp comparison method makes it possible not only to present the specifics of the coin manufacturing technology, but also to determine many parameters of monetary circulation in various states at different stages of their development based on the determination of the number of stamps used for their minting and, accordingly, the number of coins minted. This method was developed primarily in the framework of the study of an-cient numismatics, mainly the Roman Republican mint. In the context of the problem, the analysis of the coinage of the triumviri monetales 82 BC, in particular by P. Crepusius and L. Censorin, is of particular importance. The research results of foreign scientists may well form the basis for the reconstruction of the activities of the mints of the Golden Horde. Ma-terials and methods. The realization of research objectives was achieved on the basis of the dialectical method of cognition of historical processes, which includes the principles of his-toricism, objectivity and consistency. When studying the topic, it is necessary to use an in-terdisciplinary approach and, in particular, data from various auxiliary historical disciplines, in particular, numismatics, paleography, and metrology. Results. The article analyzes the works of foreign and domestic researchers related to the use of the method of stamp analy-sis in ancient and Golden Horde numismatics. The main factors of the use of stamp analysis of coins for modeling various aspects of economic development and reconstruction of vari-ous processes of historical reality are considered on the example of the activities of the mint of the city of Mokhshi. Conclusions. The use of the stamp comparison method can help in attributing Mokhshi dangs and pools, clarifying their dating, and determining the issuer’s name. Establishing the number of coins issued will not only provide an opportunity to draw interesting conclusions about the development of trade and trade relations, but also, based on the monetary circulation of the Volga region, will make it possible to determine the influence of the district center on the nearest district, will make it possible to closely study the number of people living in this district and the problem of Golden Horde demography in general.